Improving Digital Literacy to Strengthen Religious Moderation in A Multi-Religious Environment - Ramadhan, Mochammad Rizal (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Digital literacy is very important to do today. This is because fake news, especially those related to religion, spreads quickly and easily through social media. If digital literacy is strong, fake news will be easily recognized, the credibility of the source will be tested, and the context of the content viewed will be understood. This study uses a qualitative methodology and literature review to show the function of digital literacy in the context of religious moderation education. Data collection was carried out by analyzing various related libraries, including books, journals, papers, and trusted internet sources. The findings of this study indicate that digital literacy can increase a person's critical awareness of circulating information and strengthen a person's capacity to distinguish between fiction and reality. This study concludes that increasing digital literacy in strengthening religious moderation can encourage respect for diversity, tolerance, and positive interfaith communication and can help create a more inclusive and peaceful society and limit the spread of religious-based fake news. Therefore, strengthening digital literacy in teaching religious moderation is a step that must be taken to build a more critical and tolerant society